ZMAGOSLAVJE SMRTI JAEZA VAJKARDA VALVASORJA (Филолошке студије, 2019)
The Triumph of Death by Janez Vajkard Valvasor, used as the introductory illustration to his Theatrum Mortis Humanae tripartitum (1682), has so far attracted little attention of Slovenian art historians despite its interesting iconography. The single relevant iconographic analysis by Emilijan Cevc emphasises the northern character of Valvasor's work and asserts as important iconographic influence the scenes from contemporary liturgical drama, notably those enacted during the Palm processions. Cevc specially foregrounded the Škofja Loka Passion Play (1721) although it originated some forty years after the Theatrum. The comparison of the print with the processions reveals that the search for possible common points with the Škofja Loka Passion Play and similar passion plays would be futile especially in the light of the fact that there are many iconographic elements in the print pointing towards the Italian iconography of the Triumph of Death. Furthermore, it can be stated with great certainty that the motive is close to the Petrarch's Trionfo della Morte, as known from the illustrated edition of his Trionfi. Elements such as Death on a triumphal carriage with an architecturally formed catafalque, the accompanying skeletons and introduction of exotic elements in the picture are typical of Italian and notably Petrarchan iconography. A further proof of Valvasor's susceptibility to Italian influence is the architectural background against which the scene is set. The picturesque ruins, the motif of a triumphal arc, and the Egyptian obelisk on a classically formed base all contribute to a scene in which one can sense the echo of an imaginary baroque veduta with Roman ruins. Besides the unambiguous influence of Petrarchan iconography another overlooked fact should be taken into consideration, namely that The Triumph of Death is an ilustration of Valvasor's original writing, and that Valvasor himself, in the prologue to Theatrum Mortis Humanae tripartitum, provides a key to the iconographic anaylsis of the engraving.